Post‑traumatic stress disorder (PTSD) in mid‑age and older adults difers by immigrant status and ethnicity, nutrition, and other determinants of health in the Canadian Longitudinal Study on Aging (CLSA) - Davison, Karen M.; Hyland, Christina E.; West, Meghan L.; Lin, Shen (Lamson); Tong, Hongmei; Kobayashi, Karen M.; Fuller‑Thomson, Esme (My University, 2021)
This study aimed to address knowledge gaps about post-traumatic stress disorder (PTSD) in mid-age and older adults, with particular attention to the relationship of PTSD with nutrition and with ethnicity and immigrant status.
Keywords: older adults; immigration; ethnicity; determinants of health; nutrition; CLSA; post-traumatic stress disorder; PTSD A